MANAJEMEN SARANA DAN PRASARANA DI MTs DAARUL MA’ARIF BATUJAYA - Jamil, Zam zam; Sariwati, Nova; Erihadiana, Mohamad; Jahari, Jaja (STAI Al Badar Cipulus Purwakarta, 2023)
Facilities and infrastructure support the learning process so that it can run effectively. But not a few we find that some schools still have problems in the learning process due to the absence of adequate facilities and infrastructure. The management of facilities and infrastructure is very important because with the management of the facilities and infrastructure of educational institutions, their use will be maintained and clear. Therefore the need for the role and attention of the government in the management of facilities and infrastructure at each school in Indonesia in order to create successful and comfortable learning. So this study aims to determine how the management of facilities and infrastructure at MTs Daarul Ma’arif